2016
DOI: 10.1111/1755-0998.12583
|View full text |Cite
|
Sign up to set email alerts
|

Restriction site associated DNA (RAD) for de novo sequencing and marker discovery in sugarcane borer, Diatraea saccharalis Fab. (Lepidoptera: Crambidae)

Abstract: We present the development of a genomic library using RADseq (restriction site associated DNA sequencing) protocol for marker discovery that can be applied on evolutionary studies of the sugarcane borer Diatraea saccharalis, an important South American insect pest. A RADtag protocol combined with Illumina paired-end sequencing allowed de novo discovery of 12 811 SNPs and a high-quality assembly of 122.8M paired-end reads from six individuals, representing 40 Gb of sequencing data. Approximately 1.7 Mb of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…RAD tag sequencing is a cost-effective and rapid method for discovering DNA markers, especially for non-model species with no prior genome references [ 47 , 48 , 49 , 50 , 51 ]. The method enabled the identification of 19,148 SNP and 223,200 SSR motifs from 48 weevils.…”
Section: Discussionmentioning
confidence: 99%
“…RAD tag sequencing is a cost-effective and rapid method for discovering DNA markers, especially for non-model species with no prior genome references [ 47 , 48 , 49 , 50 , 51 ]. The method enabled the identification of 19,148 SNP and 223,200 SSR motifs from 48 weevils.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sugarcane borer has a wide distribution across the Western Hemisphere (Dyar & Heinrich, 1927), it is treated as a single species and its identification relies on morphological characteristics despite the high variability shown in these traits between populations (Dyar & Heinrich, 1927;Francischini et al, 2017;Pashley et al, 1990). Several studies have developed molecular markers to provide a solid differentiation from other species of the same genus (Bravo et al, 2008;Francischini et al, 2017;Joyce et al, 2016;Pavinato et al, 2013;Pavinato et al, 2017) and to investigate the genetic variation among populations of D. saccharalis (Joyce et al, 2014;Joyce et al, 2016;Silva-Brandão et al, 2015). Geographical comparisons using individuals from the southeastern United States and Argentina have also suggested that the species might be treated as a cryptic species complex due to the significant genetic divergence among lineages (Fogliata et al, 2019;Joyce et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The restriction site-associated DNA (RAD-seq) method can identify polymorphic variants in genomic regions (Miller et al 2007 ; Zhou et al 2015 ), and has been proven to be particularly suitable for species without reference genome (Wang et al 2017 ; Verdu et al 2016 ). It can provide thousands of genome-scale SNP sites (Pavinato et al 2017 ; Wang et al 2017 ) that have successfully revealed valuable information for phylogeny (Razkin et al 2016 ; Wagner and Wagner. 2017 ), phylogeography (Jeffries et al 2016 ), population genetics (Ellegren 2014 ; Shih et al 2018 ) and species identification (Herrera and Shank.…”
Section: Introductionmentioning
confidence: 99%